2006
DOI: 10.4049/jimmunol.177.12.8365
|View full text |Cite
|
Sign up to set email alerts
|

Lunatic Fringe Controls T Cell Differentiation through Modulating Notch Signaling

Abstract: T cells differentiate from bone marrow-derived stem cells by expressing developmental stage-specific genes. We here searched arrays of genes that are highly expressed in mature CD4−CD8+ (CD8 single-positive (SP)) T cells but little in CD4+CD8+ (double-positive (DP)) cells by cDNA subtraction. Lunatic fringe (Lfng), a modulator of Notch signaling, was identified to be little expressed in DP cells and highly expressed in CD8SP T cell as well as in CD4−CD8− (double-negative (DN)) and mature CD4+CD8− (CD4SP) T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 54 publications
(56 reference statements)
1
32
0
Order By: Relevance
“…Alternatively, the interaction of Notch and Notch ligands might be controlled by modifying the sugar pattern of Notch by fringe genes. The fringe-mediated addition of N-acetylglucosamine to o-fucose moieties on Notch could change the ligand sensitivity of Notch (22)(23)(24). In support of this, we have observed that NK cells express fringe genes (data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…Alternatively, the interaction of Notch and Notch ligands might be controlled by modifying the sugar pattern of Notch by fringe genes. The fringe-mediated addition of N-acetylglucosamine to o-fucose moieties on Notch could change the ligand sensitivity of Notch (22)(23)(24). In support of this, we have observed that NK cells express fringe genes (data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…9C). We suggest that rfng overexpression caused ectopic pronephrogenesis by promoting Notch signalling, as has been described in other systems (Hicks et al, 2000;Tsukumo et al, 2006). Promotion of pronephric Notch signalling activates wnt4 expression, the protein product can be secreted in more distal positions than those found normally, thus producing ectopic proximal pronephros cell fates in distal regions.…”
Section: Overexpression Of Rfng Induces Expression Of Components Of Tmentioning
confidence: 64%
“…In conclusion, Rfng promotes formation of the proximal pronephros and suppresses distal pronephrogenesis. In vertebrates, Fringe proteins promote Notch-ligand interactions (Haines and Irvine, 2003;Hicks et al, 2000;Tsukumo et al, 2006). We have shown that Wnt-4 acts downstream of Notch signalling (see above), thus we wished to confirm that Rfng also acted upstream of Wnt-4.…”
Section: Overexpression Of Radical Fringe Causes Ectopic Formation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Although some studies suggest that knockout mutants for all 3 Fringes (in a specific genetic background) do not display more developmental malformations than single mutants for Lunatic Fringe, 32 it is well established that different Fringe homologs modulate particular Notch-mediated biologic processes in a specific manner, [33][34][35] such is the case of Lunatic Fringe in the hematopoietic lineage commitment and differentiation. [36][37][38][39] Another modification involving the extracellular domain of the Notch receptor is its O-glucosylation mediated by the O-glucosyltransferase (Poglut), Rumi. 40 However, the biochemical effects of this modification are mainly unknown, but it has been suggested that it might regulate the proper folding of Notch that is required for its efficient activation.…”
Section: Notch Ligandsmentioning
confidence: 99%